2022
DOI: 10.15452/cejnm.2022.13.0014
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between postpartum stress disorder and maternal anxiety in different types of delivery (vaginal and cesarean section)

Abstract: Aim: Post-traumatic stress disorder refers to a person's experience of a traumatic event. Traumatic experiences during childbirth can cause postpartum stress in some women. The present study aimed to investigate the correlation between postpartum stress disorder in different types of delivery (normal vaginal delivery and cesarean section) and maternal anxiety. Design: This was a cross-sectional study. Methods: This cross-sectional study was performed on 714 pregnant mothers selected via cluster sampling six-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…These results are in line with research which found that the mean score of obvious anxiety and hidden anxiety were significantly higher in the group of pregnant women who had normal vaginal birth compared to the group of pregnant women with cesarean section [22]. However, another study stated differently, that type of previous delivery whether vaginal delivery or caesarean section did not affect anxiety about the current pregnancy and birth [23]. A negative birth experience or previous operative delivery is the strongest predictor of fear of childbirth in multiparous women [24] where pregnant women's mean anxiety score correlates with fear of childbirth [25].…”
Section: Overview Of Characteristics Of Pregnant Womensupporting
confidence: 89%
“…These results are in line with research which found that the mean score of obvious anxiety and hidden anxiety were significantly higher in the group of pregnant women who had normal vaginal birth compared to the group of pregnant women with cesarean section [22]. However, another study stated differently, that type of previous delivery whether vaginal delivery or caesarean section did not affect anxiety about the current pregnancy and birth [23]. A negative birth experience or previous operative delivery is the strongest predictor of fear of childbirth in multiparous women [24] where pregnant women's mean anxiety score correlates with fear of childbirth [25].…”
Section: Overview Of Characteristics Of Pregnant Womensupporting
confidence: 89%
“…Like any surgery, a cesarean section carries certain risks for both the mother and the newborn. According to an study conducted in Iran on a sample of 714 mothers, there was no statistically signi cant difference in stress levels between mothers who had vaginal delivery and those who had a cesarean section [9]. The lowest total maternal stress experience score, however, was found speci cally among mothers who delivered naturally by vaginal delivery.…”
Section: The In Uence Of Mode Of Delivery On Experiencing Stress In M...mentioning
confidence: 98%